Communication strategies in the prevention of type 2 and gestational diabetes in vulnerable groups: protocol for a scoping review - Breuing, Jessica (Syst Rev, 2019)
BACKGROUND: The global prevalence of diabetes mellitus is nearly 9%, with an upward trend in type 2 and gestational diabetes mellitus (T2DM/GDM). Evidence shows that vulnerable groups are affected disproportionally. Therefore, there is an increasing need to implement policies to prevent risk factors for T2DM/GDM and to promote a healthy lifestyle. However, up to now, no gold standard in terms of communication strategies and/or public awareness campaigns is known. METHODS/DESIGN: We will conduct a systematic scoping review to evaluate communication strategies in the prevention of T2DM/GDM in vulnerable groups. Two reviewers will independently screen the results of the electronic literature search in PubMed, EMBASE, PsycINFO, PSYNDEX, Social Science Citation Index, and CINAHL. Extracted data will be charted, categorized, and summarized. DISCUSSION: The results will be used to inform the National education and communication strategy on diabetes mellitus in Germany. In particular, the results will be discussed in focus groups of experts to develop recommendations for communication strategies. SYSTEMATIC REVIEW REGISTRATION: PROSPERO does not register scoping reviews.